Seed of Sarah: Memoirs of a Survivor - Isaacson, Judith Magyar
This gripping and highly acclaimed account of a young woman's experience in concentration camps now includes a final chapter, "A Time to Forgive?" detailing the author's trips back to her former forced labor camp in Germany.
Keywords: Isaacson, Judith Magyar, -- 1925-2015.; Auschwitz (Concentration camp); Jews -- Persecutions -- Hungary -- Kaposvár.; Holocaust, Jewish (1939-1945) -- Hungary -- Kaposvár -- Personal narratives.; Kaposvár (Hungary) -- Ethnic relations.; Women.; BIOGRAPHY & AUTOBIOGRAPHY.; Holocaust.; Electronic books.